Study Effect of the COVID-19 Lockdown on the Transition from Mild Cognitive Impairment to Dementia - Padhiar, Jigar Sanjiv; Rai, Uddipak; Singh, Reema (National Journal of Community Medicine, 2025)
Background: Dementia represents a significant global health challenge, contributing to high fatality and frailty rates. The worldwide prevalence of dementia is projected to increase by 150% from 2018 to 2051. Countries with low to moderate incomes are expected to experience demographic shifts starting in 2017. The impact of the COVID-19 pandemic on cognitive decline is unclear, but increased social engagement is associated with a lower risk of dementia. We hypothesized that the first nationwide lockdown would lead to a rise in dementia diagnoses, accelerate cognitive decline in at-risk populations, and alter diagnostic patterns due to limited healthcare access. Methodology: Data collection continued via telephone or audio-video calls during lockdowns, excluding participants with pre-existing dementia. Mild cognitive impairment (MCI) was defined using established criteria, with Clinical Dementia Rating (CDR) scores of 0.5 and Mini-Mental State Examination (MMSE) scores between 24 and 27. Poisson regression with cubic splines adjusted for age was used to estimate dementia incidence before and after 01-Mar-2020. Results: Among 2140 participants, 200 were diagnosed with dementia before 20-Mar-2020, and 40 after. The incidence rate post-lockdown was not significantly different (p = 0.470). Secondary analysis revealed a decreased association between MCI and dementia after February 2020 (p = 0.021). Conclusion: Dementia prevalence did not significantly change after the first lockdown. However, the relationship between MCI and dementia incidence weakened, possibly indicating faster progression to dementia or diagnostic challenges due to remote assessments.